Vocabulary for listening: Emerging evidence for high and mid-frequency vocabulary knowledge. (February 2018) - Matthews, Joshua
Abstract: This article presents empirical evidence aimed at informing approaches to vocabulary development for the purpose of supporting L2 listening comprehension. Inferential statistics were used to analyze the relationship between second language (L2) aural vocabulary knowledge (AVK), L2 listening comprehension and the overall L2 proficiency among 247 tertiary level L2 learners of English. Three frequency based levels of AVK were measured. Measures of level 1 (0–2000 frequency range) and level 2 words (2001–3000 frequency range) tapped AVK of high frequency words, and level 3 words (3001–5000 frequency range) tapped AVK of words just beyond the high frequency range. Listening comprehension was measured with a version of the International English Language Testing System (IELTS). Regression modeling showed that AVK at each of the three levels contributed uniquely to the prediction of L2 listening for the entire cohort. Only measures of level 2 and 3 AVK were uniquely predictive of L2 listening for a relatively high proficiency subgroup, whereas only level 1 AVK offered a unique contribution to the prediction of L2 listening scores for a relatively low proficiency subgroup. Results are interpreted in order to provide a range of pedagogical recommendations. Highlights: L2 aural vocabulary knowledge is predictive of L2 listening comprehension. Knowledge of high frequency words is predictive of lower proficiency learners' L2 listening comprehension. Knowledge of high and mid-frequency words is predictive of higher proficiency learners' L2 listening comprehension.